2013
DOI: 10.1097/yic.0b013e32835ba832
|View full text |Cite
|
Sign up to set email alerts
|

Changes in prolactin levels and sexual function in young psychotic patients after switching from long-acting injectable risperidone to paliperidone palmitate

Abstract: Hyperprolactinaemia is a significant side effect of antipsychotic medications and may cause sexual dysfunction. The aim of our study was to assess the effect of switching from long-acting injectable (LAI) risperidone to paliperidone palmitate (PP) on sexual function and prolactin levels in patients with psychosis. We carried out a prospective observational study during a 3-month period that involved 11 patients with psychosis treated with risperidone-LAI who suffered from hyperprolactinaemia and who were then … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 5 publications
1
16
0
2
Order By: Relevance
“…Across all the studies, the proportion of subjects who experienced potentially prolactinrelated AEs (i.e. amenorrhea/gynecomastia/galactorrhoea) was below 4% for all dose groups (3mg, 6mg, 9mg and 12mg) [142].…”
Section: Adverse Effectsmentioning
confidence: 99%
“…Across all the studies, the proportion of subjects who experienced potentially prolactinrelated AEs (i.e. amenorrhea/gynecomastia/galactorrhoea) was below 4% for all dose groups (3mg, 6mg, 9mg and 12mg) [142].…”
Section: Adverse Effectsmentioning
confidence: 99%
“…As paliperidone is the major active metabolite of risperidone, the mechanism of PRL elevation for paliperidone is likely similar to that of risperidone [260262]. However, two recently published studies suggest that PRL levels seem to decrease after switching from risperidone to paliperidone in patients with a psychotic disorder [263, 264]. An analysis of abnormal PRL values in ten randomized clinical trials, including 3,173 patients treated with paliperidone palmitate, showed that, overall, at any time, PRL levels were elevated for 38.8 % of the subjects [265].…”
Section: Prl and Antipsychoticsmentioning
confidence: 99%
“…Further studies support this claim, as young males treated with risperidone reported diminished sexual function in comparison to those not treated with antipsychotics . Haloperidol shows similar effects to risperidone, as one study reported a high of 77 ng/mL in a study population .…”
Section: Discussionmentioning
confidence: 88%